Environmental awareness on solid waste management practices: A case study in Angolan secondary schools - Talita Ima Panzo; José Carlos Góis; José Manuel Mendes (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
This paper presents a case study on the environmental awareness of the students of secondary schools in Angola and analyses the environmental education programs in the two cycles. The study was carried out in the four largest provinces of Angola and the results were obtained from questionnaires to the students and interviews with the school coordinators and the waste management officers in the region. The results show that the students have moderate consumption habits of electricity and water, demonstrated by 40% of students following the appropriate attitude, and have reasonable knowledge about the scenarios that produce large environmental impact, marking 3 out of 9 options: river pollution, toxic waste in the soil and sewage discharge on the beach as the most relevant, together reaching almost 50% of the responses. However, they have a gap in knowledge about the health impact of solid waste disposal in dumps site close to urban areas, as evidenced by the high number of children and adolescents living near these areas and with some of them helping their families as waste pickers. The poor environmental education program and the nonexistence of school activities on these issues contribute for disassociate the linkage of waste disposal in dumps with diseases. As waste disposal in dumps is current in almost all provinces in Angola, except Luanda, environmental education in schools plays an important role in preparing children and adolescents to adopt practices in the future that protect the environment and contribute to the reduction of public health problems. In addition, children and adolescents can indirectly influence their parents on these issues.